MORAL VALUES IN âTHE HUNGER GAMESâ NOVEL TO BUILD STUDENTSâ CHARACTER - Himmah, Atikatul; SaÃ¢Â€Â™adiyah, Evha Nazalatus (Jurnal al Hikmah, 2017)
Nation should be build by putting character building in the first place, since this character building that will make Indonesia become a big, glorious and victorious and prestige country. This study aimed to (1) describe the moral values in The Hunger Games Novel, (2) describe the moral values in The Hunger Games Novel that could be implemented to build studentsâ character. The result of the research is that there are some moral values in The Hunger Games Novel that could be implemented to build studentsâ character which are independent, friendly, work hard, discipline, love science, responsible, social care and appreciate achievement. The implementation of character education is not enough if only implemented in school or education. On the next phase, character education should be implemented in society, government agency, society organization, non-governmental organization, company and other group society. Keywords: moral values, character education, The Hunger Games Novel